Testing neoclassical competitive market theory in the field - List, John A. (National Academy of Sciences, 2002)
This study presents results from a pilot field experiment that tests predictions of competitive market theory. A major advantage of this particular field experimental design is that my laboratory is the marketplace: subjects are engaged in buying, selling, and trading activities whether I run an exchange experiment or am a passive observer. In this sense, I am gathering data in a natural environment while still maintaining the necessary control to execute a clean comparison between treatments. The main results of the study fall into two categories. First, the competitive model predicts reasonably well in some market treatments: the expected price and quantity levels are approximated in many market rounds. Second, the data suggest that market composition is important: buyer and seller experience levels impact not only the distribution of rents but also the overall level of rents captured. An unexpected result in this regard is that average market efficiency is lowest in markets that match experienced buyers and experienced sellers and highest when experienced buyers engage in bargaining with inexperienced sellers. Together, these results suggest that both market experience and market composition play an important role in the equilibrium discovery process.